UJI PRAKTIKALITAS PERANGKAT PERCOBAAN KONSEP HUKUM FARADAY UNTUK PEMBELAJARAN FISIKA DI KELAS XII SMA - Ilham Dwi Oetomo; Yennita Yennita; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to examine the practicality of faraday legal symptom experimental devices as a medium for high school physics learning. The research method used is research and development. In this study faraday legal experimental devices were tested on 20 students and 2 teachers MAN 1 Pekanbaru. Based on the data analysis, the practicality of the experimental device according to the teacher was obtained that the experiment tools and LKPD could help facilitate the teachers in the faraday legal learning process by obtaining the practicality value of the products in the very high category. The results of practical tests according to students, the experimental device provides convenience in studying the laws of faraday with the acquisition of practical scores in the very high category. Based on the data obtained, the experimental tools and student worksheets are very practical for students and teachers to use in the learning process.Key Words: Faraday law, student worksheets, practicality.